Antiviral effects of artesunate on JC polyomavirus replication in COS-7 cells - Sharma, Biswa Nath; Marschall, Manfred; Rinaldo, Christine Hanssen (Antimicrobial Agents and Chemotherapy, 2014)
The human JC polyomavirus (JCPyV) causes the fatal demyelinating disease progressive multifocal leukoencephalopathy (PML). A growing number of patients with induced or acquired immunosuppression are at risk for infection, and no effective antiviral therapy is presently available. The widely used antimalarial drug artesunate has shown broad antiviral activity in vitro but limited clinical success. The aim of this study was to investigate the effect of artesunate on JCPyV replication in vitro. The permissivity for JCPyV MAD-4 was first compared in four cell lines, and the monkey kidney cell line COS-7 was selected. Artesunate caused a concentration-dependent decrease in the extracellular JCPyV DNA load 96 h postinfection, with a 50% effective concentration (EC50) of 2.9 ?M. This effect correlated with a decreased expression of capsid protein VP1 and a reduced release of infectious viral progeny. For concentrations of <20 ?M, transient reductions in cellular DNA replication and proliferation were seen, while for higher concentrations, some cytotoxicity was detected. A selective index of 16.6 was found when cytotoxicity was calculated based on cellular DNA replication in the mock-infected cells, but interestingly, cellular DNA replication in the JCPyV-infected cells was more strongly affected. In conclusion, artesunate is efficacious in inhibiting JCPyV replication at micromolar concentrations, which are achievable in plasma. The inhibition at EC50 probably reflects an effect on cellular proteins and involves transient cytostatic effects. Our results, together with the favorable distribution of the active metabolite dihydroartemisinin to the central nervous system, suggest a potential use for artesunate in patients with PML.
EVALuna2:8233